Topographic anatomy of the spleen in children and adolescents according to intravital imaging - A. S. Lozinskiy (Сибирский научный медицинский журнал, 2025)
The aim of the study was to establish age and gender patterns of topographic anatomy of the spleen in children and adolescents based on intravital imaging data.   Material and methods. Computed tomograms of the abdominal cavity of 88 children and adolescents without visible pathology of the abdominal organs were analyzed. The subjects were divided into 4 age groups: early, first and second childhood, and adolescence. The distance from the spleen to the median sagittal plane, the distance from the spleen to the abdominal organs, the skeletotopy of the spleen and the distance from the spleen to the surface of the body were determined.   Results and discussion. A significant increase in the distance from the spleen to the median sagittal plane with age was found. In the first three age groups, the value of the indicator was higher for girls compared to boys, and lower in adolescence. A significant increase in the distance from the spleen to the liver, pancreas, aorta, inferior vena cava, and loops of the jejunum and ileum was determined from early childhood to adolescence; in individuals of the first and early childhood ages, the distance to the liver, pancreas, aorta, and inferior vena cava was the same, while in adolescents it was greater than in those examined in the second childhood. Within one group, no differences were found between the indicators for girls and boys. Skeletotopically, the spleen tended to be located lower with age. The upper pole of the spleen in the overwhelming majority of cases descended from ThIX to the intervertebral disc ThX–ThXI, the hilum of the spleen ‒ from ThXII to the intervertebral disc ThXII–LI, the lower pole ‒ from LI to the intervertebral disc LI–LII. The distance from the spleen to the body surface significantly increased from early childhood to adolescence along the anterior median, left middle axillary and left scapular lines; in individuals of the first and early childhood ages it was the same, in children of the second childhood and adolescence it increased in comparison with previous age periods. In the adolescent group, the indicator was higher among boys than among girls along the anterior median, left middle axillary and left scapular lines.   Conclusions. The article presents the topographic and anatomical characteristics of the spleen in children and adolescents and establishes patterns of change taking into account the sex and age of the subjects.